DAMPAK MEDIA SOSIAL BAGI PERKEMBANGAN KOGNITIF REMAJA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Cahya Nabila, Husniyah; Iqbal Amar Muzaki; M.Makbul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social media has now become a crucial component in the lives of young people and has a significant impact on their cognitive development and behavior. This study aims to analyze the impact of social media on adolescents’ cognitive development from the perspective of Islamic education. This research adopts a qualitative approach through a library research method supported by an interview with a student from the State Islamic University (UIN) Bandung. The data were collected from various literature sources, including academic journals, books, and relevant articles, as well as interview results related to adolescents’ use of social media platforms. The data analysis technique used was descriptive-analytical, conducted by reviewing, classifying, and interpreting the research findings. The results show that social media provides positive impacts, such as expanding social networks, facilitating communication, accelerating the flow of information, and functioning as a learning tool. However, social media platforms can also produce negative effects when used excessively, including reduced learning concentration, social media addiction, lower self-confidence due to social comparison, and the risk of exposure to inappropriate content and cyberbullying. From the perspective of Islamic education, the use of social media should be accompanied by principles such as tafakkur (deep reflection), tabayyun (verification of information), and the wise use of intellect (‘aql) so that social media can be utilized effectively and contribute positively to adolescents’ cognitive development.